Ethno-ecological household of the Kalmyks in the beginning of 20th century - Badmaeva, Nogan V.; Idzhaeva, Bayra V. (The New Research of Tuva, 2014)
The article overviews traditional household of the Kalmyks at the beginning of 20th century within the framework of reasonable use of natural resources, kinds of traditional household, reasons of a modern disastrous ecological situation in the region.